A Bibliometric Analysis of the Evolution and Diffusion of Climate Finance Literature - Judijanto, Loso; Dama , Desi Putri; Lesmana, Tera (West Science Social and Humanities Studies, 2025)
This study conducts a comprehensive bibliometric analysis to examine the intellectual structure, evolution, and diffusion of climate finance literature from 2000 to 2024. Drawing data from the Scopus database, the study applies co-authorship, citation, keyword co-occurrence, and country collaboration analyses using VOSviewer. The findings reveal that climate finance and climate change are central themes, anchoring an interdisciplinary knowledge network that encompasses economic, policy, justice, and innovation-related subfields. Temporal analysis shows a progression from early focus on emissions and treaties toward recent interest in green bonds, financial innovation, and climate risk. Key contributors and collaborative hubs are identified, with the United Kingdom, United States, and Germany emerging as dominant producers of climate finance scholarship. Despite growing global interest, the analysis highlights regional imbalances in research production and calls for more inclusive, equitable academic collaboration. This study provides valuable insights for future research and policy formulation by mapping the trajectory and scope of the climate finance discourse.